Surgical Management of Chronic Tendoachilles Tear in Elderly Patients – A Case Series - Mahajan, Neetin P (J Orthop Case Rep, 2021)
INTRODUCTION: Chronic tendoachilles (TA) tears are commonly missed injuries in elderly population with associated comorbidities and they usually occur as low-energy injuries. Appropriate surgical management helps in getting a better functional outcome in elderly patients. CASE SERIES: We present a series of three cases of chronic TA tear in elderly patients managed surgically. Two patients had an insertional tear and they were managed with flexor hallucis longus (FHL) transfer and fixed with interference screw in the calcaneum. Another patient was managed with end-to-end suturing using fiber wire. All the patients are having good functional outcome without any wound complication or re rupture. CONCLUSION: Early diagnosis, meticulous repair, and handling of soft tissues and TA tear help in getting a better outcome in elderly patients. The final functional outcome depends on intraoperative stability of the repair, ankle physiotherapy, and wisely selection of the treatment method, which mainly depends on the location of the tear. Reconstruction with FHL tendon using interference screw in calcaneum helps to repair the insertional tears in elderly patients.